2010
DOI: 10.1186/1752-1947-4-44
|View full text |Cite
|
Sign up to set email alerts
|

Melaena with Peutz-Jeghers syndrome: a case report

Abstract: IntroductionPeutz-Jeghers syndrome (PJS) is a rare familial disorder characterised by mucocutaneous pigmentation, gastrointestinal and extragastrointestinal hamartomatous polyps and an increased risk of malignancy. Peutz-Jeghers polyps in the bowel may result in intussusception. This complication usually manifests with abdominal pain and signs of intestinal obstruction.Case PresentationWe report the case of a 24-year-old Caucasian male who presented with melaena. Pigmentation of the buccal mucosa was noted but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Although most of pigmentations of PJS are located around of mouth cheek, nostril, periorbital, ears, and overall orifices of body [ 3 ], these pigmentations of our patient were located intraorally in buccal and labial mucosa. Also Mozaffar et al reported a PJS without mucocutaneous pigmentation [ 6 ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although most of pigmentations of PJS are located around of mouth cheek, nostril, periorbital, ears, and overall orifices of body [ 3 ], these pigmentations of our patient were located intraorally in buccal and labial mucosa. Also Mozaffar et al reported a PJS without mucocutaneous pigmentation [ 6 ].…”
Section: Discussionmentioning
confidence: 82%
“… A family history of PJS with characteristic mucocutaneous pigmentation. Characteristic mucocutaneous pigmentation with any number of polyps [ 3 ]. …”
Section: Introductionmentioning
confidence: 99%
“…The most common and concerning manifestation in children and adolescents is the occurrence of small bowel intussusception, which could represent a serious surgical emergency and be life-threatening. 1,2 We report in this paper the case of recurrent intestinal intussusceptions in a child, resulting of hamartomatous Peutz-Jeghers polyps. Our aim was to remind diagnostic and management particularities of this unusual condition and to highlight the importance of regular follow-up for these patients to avoid complications.…”
Section: Introductionmentioning
confidence: 95%
“…[1234567] Germline-inactivating mutations in one allele of the STK11/LKB1gene at chromosome 19p13.3 have been found in most Peutz–Jegher's syndrome. [89101112] Genital tract neoplasms in the female patients with PJS include ovarian neoplasms from the epithelium and stromal cells, adenoma malignum of the cervix, and adenocarcinomas of the endometrium.…”
Section: Introductionmentioning
confidence: 99%